1993
DOI: 10.1007/bf02374489
|View full text |Cite
|
Sign up to set email alerts
|

Storage temperature and differing methods of sample preparation in the measurement of urinary albumin

Abstract: Microalbuminuria is a predictor of persistent proteinuria, renal failure and cardiovascular disease and therefore accurate determination of urinary albumin concentration is important. We examined the stability of albumin in urine under different conditions of storage, temperature and sample preparation. There was no significant difference in urinary albumin concentration between fresh urine and urine stored at either 4 degrees C or 20 degrees C for up to 7 days. Similarly in urine samples from diabetic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 27 publications
2
20
3
Order By: Relevance
“…Results of the present study are in agreement with previous studies that describe no significant change in uALB concentration after storage at 220uC for up to 6 months. 3,7 However, others detected a decrease of 20% in uALB concentration after 6 months at 220uC. 26 In the present study, uRBP was significantly lower at T 4 months compared with T 0 .…”
Section: Discussioncontrasting
confidence: 51%
“…Results of the present study are in agreement with previous studies that describe no significant change in uALB concentration after storage at 220uC for up to 6 months. 3,7 However, others detected a decrease of 20% in uALB concentration after 6 months at 220uC. 26 In the present study, uRBP was significantly lower at T 4 months compared with T 0 .…”
Section: Discussioncontrasting
confidence: 51%
“…Innanen et al (21 ) and Collins et al (22 ) found no substantial difference after 6 months. Two authors reported no substantial change in UAC after 24 (29 ) and 26 months (30 ); the UACs in those studies, however, were considerably higher than in ours.…”
Section: Clinical Chemistry 51 No 11 2005mentioning
confidence: 91%
“…Moreover, storage tube materials might play a role in preventing albumin loss after freezing. Collins et al (22 ), however, found no difference in concentration when they studied the effect of different tube materials on UAC after freezing. Conformational changes that occur during freezing may lead to loss of the antibody recognition site that is needed to measure albumin with immunochemical methods (22,32 ).…”
Section: Clinical Chemistry 51 No 11 2005mentioning
confidence: 97%
“…A fasting blood sample was taken for measurement of plasma glucose (enzymatic colorimetry), serum total cholesterol (enzymatic colorimetry), and serum creatinine (rate reaction method) using a Cobas Mira Plus analyser (Roche Diagnostics, Basel, Switzerland). Urine creatinine (Jaffe reaction) and urine albumin concentration (by immunoturbidimetry [23]) were determined using a Cobas Mira Plus analyser (Roche Diagnostics). Glycated hemoglobin (HbA 1c ) was measured by boronate affinity high-pressure liquid chromatography (Primus CLC330, Kansas City, MO).…”
Section: Methodsmentioning
confidence: 99%